Distinct lipidomic profiles but similar improvements in aerobic capacity following sprint interval training versus moderate-intensity continuous training in male adolescents - Su, Wantang; Liu, Jianming; Wang, Aozhe; Zhang, Haifeng; Sun, Yaqi; Yan, Zhiyi; Svensson, Michael; Yu, Ji-Guo; Zhao, Li (Frontiers in Physiology, 2025)
BackgroundExercise-induced metabolic changes, especially lipidomic changes are generally associated with improvements in cardiovascular health. Despite numerous previous studies, the differences in lipidomic profile response to different types of exercise training remain unclear. This study aimed to investigate how two different exercise intensities affect aerobic capacity and serum lipidomic profiles in healthy adolescents.MethodsTwenty-four healthy untrained male adolescents (13.08 ± 0.88 years old) were recruited and randomly assigned to moderate-intensity continuous training (MICT) group or sprint interval training (SIT) group to complete a specific training on a cycle ergometer for 6 weeks. Peak oxygen uptake (VO2peak) and body composition were measured, and blood samples were collected for serum lipoproteins and lipidomic analysis. Anthropometric, VO2peak, and serum biochemical data were analyzed using two-way repeated analysis of variance, while targeted lipidomic analysis was performed by principal component analysis and paired-sample t-test.ResultsVO2peak significantly improved from 39.05 ± 8.17 to 47.52 ± 8.51 [F (1, 44) = 14.75, p < 0.05] for MICT and from 40.13 ± 6.37 to 48.42 ± 7.01 [F (1, 44) = 14.75, p < 0.05] for SIT. A total of 28 lipids in MICT and 5 lipids in SIT showed significant changes out of 276 identified lipids (FC > 1.5 or <1/1.5, FDR <0.05). In MICT, 21 lipids, including sphingolipid (SP) and phospholipid (PL), decreased, while 7 lipids increased. In SIT, all 5 lipids, which were free fatty acid (FFA), decreased.ConclusionAlthough both MICT and SIT induced similar and significant improvements in VO2peak, serum lipid adaptations to the training differed. The primary changes in serum lipidomic intermediates for both types of training were reductions; however, SIT affected FFA, while MICT predominantly influenced SPs and PLs.